Evaluation of the Single-component Thermal Dust Emission Model in Cosmic Microwave Background Experiments - Hao Liu; Jia-Rui Li; Yi-Fu Cai (The Astrophysical Journal Supplement Series)
It is well known that multiple Galactic thermal dust emission components may exist along the line of sight, but a single-component approximation is still widely used, since a full multicomponent estimation requires a large number of frequency bands that are only available with future experiments. In light of this, we present a reliable, quantitative, and sensitive criterion to test the goodness of all kinds of dust emission estimations. This can not only give a definite answer to the quality of current single-component approximations but also help determine preconditions of future multicomponent estimations. Upon the former, previous works usually depend on a more complicated model to improve the single-component dust emission; however, our method is free from any additional model, and is sensitive enough to directly discover a substantial discrepancy between the Planck High Frequency Instrument data (100–857 GHz) and associated single-component dust emission estimations. This is the first time that the single-component estimation is ruled out by the data itself. For the latter, a similar procedure will be able to answer two important questions for estimating the complicated Galactic emissions: the number of necessary foreground components and their types.